Active control of doubly curved laminated composite shells using elliptical smart constrained layer damping treatment. (July 2019) - Sahoo, S.R.; Ray, M.C.
Abstract: In this paper, performance of the smart constrained layer damping (SCLD) treatment with elliptical geometrical plan form is investigated for controlling the vibrations of various types of doubly curved composite shells. The SCLD treatment is composed of a viscoelastic layer and an advanced constraining piezoelectric composite (PZC) layer attached at the top surface of the composite shell. A mesh free (MF) model of the smart composite shell has been developed based on the element free Galerkin approach to study its dynamic behaviour within the framework of a mixed layerwise displacement field theory considering transverse extensibility. Spherical, paraboloid and hyperboloid type composite shells with antisymmetric/symmetric cross-ply as well as general angle-ply lamination sequences are considered for the analysis. The numerical results demonstrated that the elliptical SCLD patches are more efficient in attenuating the vibration of the spherical and paraboloid laminated shells while the regular rectangular/square plan form patches are effective for the hyperboloid shells. The numerical results also indicate that the elliptical patches are having higher performance index in enhancing the active damping characteristics of the composite shells. Investigations are also carried out to analyze the effect of the variation in orientation of the piezoelectric fibers in the active PZC layers in attenuating the vibration of shells. Highlights: Smart constrained layer damping (SCLD) of laminated composite shells has been investigated. Elliptical patches of active constrained layer damping treatment has been used. A three-dimensioanl element free Galerkin (EFG) model has been developed for the first time for such analyses. It is shown that the control authority of the elliptical patch is better than the square type patches.